2009
DOI: 10.1002/ajmg.a.32646
|View full text |Cite
|
Sign up to set email alerts
|

Generalized arterial calcification of infancy: Phenotypic spectrum among three siblings including one case without obvious arterial calcifications

Abstract: Generalized arterial calcification of infancy (GACI) (OMIM no. 208000) is characterized by calcification of the major arteries and soft tissues and associated with mutations in the ENPP1 gene. Most affected patients die within the first 6 months of life although prolonged survival is increasingly recognized. We report on three siblings with GACI and striking phenotypic variability. Two siblings (including the sibling survivor) were compound heterozygotes for mutations in exon 7 (c.783C>G (p.Y261X)) and exon 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 21 publications
(44 reference statements)
0
22
0
Order By: Relevance
“…(43) Also in 2009, other investigators reported their plan to stop risedronate therapy after 3 years of successful treatment of a GACI patient. (44) Hence, PPi-like effects of all BPs might reverse the AC of GACI. Of interest, nitrogen-containing BPs are now being assessed for calcific aortic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…(43) Also in 2009, other investigators reported their plan to stop risedronate therapy after 3 years of successful treatment of a GACI patient. (44) Hence, PPi-like effects of all BPs might reverse the AC of GACI. Of interest, nitrogen-containing BPs are now being assessed for calcific aortic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound showed diffusely hyperechoic abdominal aorta, common iliac arteries and renal arteries, generalized and diffuse calcification of the carotid arteries and increased echogenicity in the anterior cerebral and middle cerebral arteries, all with normal Doppler velocities. DNA sequencing of the ENPP1 gene showed a homozygous mutation in exon 14 at c.1412A>G, a mutation previously reported as disease-causing for IACI [1][2][3]. DNA analysis in each parent demonstrated heterozygosity for the same defect.…”
Section: Casementioning
confidence: 65%
“…Coronary artery involvement can be lethal within the first 6 months. Several case studies have described patients who survived into adulthood with persistent hypertension and cardiovascular squealae; however, approximately 85% of affected infants do not survive beyond 6 months of age [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myointimal proliferation is found to be associated with calcified spots, but may also occur in areas lacking calcification and vice versa. This suggests a separate pathological process involved in the development of GACI (Dlamini et al 2009). The aorta, renal, mesenteric, and carotid arteries are usually involved, while the cerebral vessels are commonly spared by the calcification process (Rutsch et al 2008).…”
Section: Discussionmentioning
confidence: 90%